2020
DOI: 10.1038/s41598-020-74995-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of GIM-TEC disturbances before M ≥ 6.0 inland earthquakes during 2003–2017

Abstract: With the rapid development of the Global Navigation Satellite System (GNSS) and its wide applications to atmospheric science research, the global ionosphere map (GIM) total electron content (TEC) data are extensively used as a potential tool to detect ionospheric disturbances related to seismic activity and they are frequently used to statistically study the relation between the ionosphere and earthquakes (EQs). Indeed, due to the distribution of ground based GPS receivers is very sparse or absent in large are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Both light and moderate earthquakes showed only 2% occurrences each in terms of total precursors found (Figure 1). Kon et al (2011) and Zhu and Jiang (2020) concur that the frequency of ionospheric TEC disturbances is directly proportional to the magnitude of the earthquake. Hence, as the magnitude of the earthquake increases, any slight rise in the occurrence rates of TEC disturbances preceding the event is more likely to be associated with the impending seismic activity (Pulinets et al, 2003).…”
Section: Magnitudementioning
confidence: 71%
“…Both light and moderate earthquakes showed only 2% occurrences each in terms of total precursors found (Figure 1). Kon et al (2011) and Zhu and Jiang (2020) concur that the frequency of ionospheric TEC disturbances is directly proportional to the magnitude of the earthquake. Hence, as the magnitude of the earthquake increases, any slight rise in the occurrence rates of TEC disturbances preceding the event is more likely to be associated with the impending seismic activity (Pulinets et al, 2003).…”
Section: Magnitudementioning
confidence: 71%
“…If the earthquake samples are analyzed together, one may not find clear results as the correlation between either negative or positive anomalies and earthquakes will decrease. This might be the reason why no significant anomalies for global earthquakes were detected in some studies (Zhu and Jiang, 2020). In addition, the RMS of GIM-TEC data is different at different places due to the uneven distribution of GPS stations.…”
Section: Discussionmentioning
confidence: 94%
“…They found that the anomalies were concentrated 1-5 days before the earthquakes and that the anomalies were most obvious near the epicenter. In similar research, Zhu and Jiang [18] statistically investigated ionospheric TEC variations 15 days before and after 276 individual inland earthquakes of M s ≥ 6.0. After excluding the disturbance of geomagnetic activity, they found differences in terms of spatial distribution, with the largest differences being in the epicentral region, whereas the incidence of ionospheric TEC disturbances in the five days before each earthquake was generally higher than that after the earthquake, and both increased slightly with the magnitude.…”
Section: Index Terms-anomalymentioning
confidence: 99%